ANALISIS PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN DI TOA BAJA KITCHEN & COFFEE CIREBON - Celine Celine; Roels Ni Made Sri Puspadewi (Cross-border, 2023)
Toa Baja Kitchen & Coffee as a restaurant in the Cirebon area, is able to attract many customers on weekdays and holidays. With so many customers coming, it will raise the question "Does Toa Baja already have a good store atmosphere?" and "Is the purchase decision increased because there is influence from the store atmosphere?". This research was conducted with the aim of knowing whether store atmosphere has an influence on purchasing decisions at Toa Baja Kitchen & Coffee Cirebon. Researchers conducted this research using quantitative descriptive research methods. The data in this study were obtained from the results of distributing questionnaires which were carried out offline or directly distributed at the Toa Baja Kitchen & Coffee Cirebon location, by distributing them to 103 respondents. The questionnaire distributed consisted of 38 statements with a Likert scale type. The results of the questionnaire were then processed with a tool in the form of SPSS version 27. The results of the research that have been obtained are that the majority of respondents are women with an age range of 20-25 years and have the most status, namely private employees. Based on validity and reliability tests, all statements used are valid and reliable. Store atmosphere can influence 64% of the purchasing decision variable at Toa Baja Kitchen & Coffee Cirebon, and others are influenced by other factors not explained in this study. Based on the simple linear regression test, the regression coefficient X shows the number 0.304, therefore for every 1% addition to the store atmosphere, the purchase decision will increase by 0.304. Through the results of the T test it can be seen that the variable store atmosphere influences purchasing decisions. Based on the results of this study, the suggestion for Toa Baja Kitchen & Coffee Cirebon is to develop a store atmosphere in terms of Exterior, General Interior and Store Layout to improve purchasing decisions at Toa Baja Kitchen & Coffee.